Coronavirus disease 2019 (COVID-19) and neurological manifestations: A potential neuroinvasive pathogen - Rissardo, Jamir; Caprara, Ana (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Coronavirus disease 2019 (COVID-19) was first described in December 2019 in Wuhan, China, and rapidly widespread and became a global concern. In this outbreak, a new beta coronavirus from the order Nidovirales, which has a positive sense and single-stranded RNA genome, was identified. Herein, we would like to highlight the neurological complications of the COVID-19 and the neuroinvasive potential of this virus. It is worthy of mentioning that COVID-19 mainly causes acute respiratory distress syndrome, which is one of the most common causes of death. However, the latest studies demonstrated that, in severe cases, neurological manifestations can occur.
Keywords: Coronavirus; neuroinvasive; neurology; pandemic